1992
DOI: 10.2307/1427480
|View full text |Cite
|
Sign up to set email alerts
|

Further monotonicity properties of renewal processes

Abstract: In a discrete-time renewal process {Nk, k = 0, 1, ·· ·}, let Zk and Ak be the forward recurrence time and the renewal age, respectively, at time k. In this paper, we prove that if the inter-renewal time distribution is discrete DFR (decreasing failure rate) then both {Ak, k = 0, 1, ·· ·} and {Zk, k = 0, 1, ·· ·} are monotonically non-decreasing in k in hazard rate ordering. Since the results can be transferred to the continuous-time case, and since the hazard rate ordering is stronger than the ordinary stochas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1992
1992
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Other monotonicities in the continuous-time setting seem not to be considered very often. See for example Kijima (1992) for the successful use of these monotonicities in the discrete-time case.…”
Section: Some Preliminariesmentioning
confidence: 99%
“…Other monotonicities in the continuous-time setting seem not to be considered very often. See for example Kijima (1992) for the successful use of these monotonicities in the discrete-time case.…”
Section: Some Preliminariesmentioning
confidence: 99%
“…In fact, Baxter (1988) has shown that (27) holds for some processes that need not be ordinary renewal processes. Some related results can be found in Kijima (1992…”
Section: Moshe Shaked and Haolong Zhumentioning
confidence: 96%
“…Thus, the relationships among the three statements in the right-hand sides of (6), (7) and (5) are of interest. In Theorem 1 it is shown that these three statements are equivalent.…”
Section: Replacement Interval Tmentioning
confidence: 99%
“…Brown's conjecture in the continuous case, however, has remained open. See Szekli (1986Szekli ( ), (1990, Hansen and Frenk (1991), Shaked and Zhu (1992), Kijima (1992), and Kebir (1997) for related results and discussions. Also relevant is the work of Lund et al (2006), who used hazard rates and renewal sequences to study reversible Markov chains.…”
Section: Introductionmentioning
confidence: 99%